Case Report: Psychogenic purpura in a uremic patient on peritoneal dialysis - Zhang, Lin; Zhang, Hanqing; Zhao, Yuetong; Zhang, Tao; Zhu, Zhengjie; Qiao, Yanheng; Tian, Yongming; Su, Hang; Li, Jie; Yang, Bo (Frontiers in Immunology, 2025)
Psychogenic purpura (Gardner-Diamond syndrome) is a rare autoimmune vasculopathy characterized by the spontaneous onset of painful edema and infiltrative cutaneous lesions that rapidly develop into ecchymosis after severe psychological stress events. In this article, we report an 87-year-old female uremic patient who was admitted to the hospital with erythema and subcutaneous ecchymoses on the head and face following an Aedes mosquito sting. She was previously diagnosed with “toxic insect stings and skin bacterial infections” and was given anti-infective treatment by an outside hospital, which was ineffective. Subsequent laboratory tests at our hospital revealed only an increase in fibrinogen and leukocytosis. Tracing the history revealed that the patient’s purpura episodes were related to a major life event, the death of her husband. After consultation with the dermatology department, the patient’s autoerythrocyte sensitization test was positive, and she was finally diagnosed with “psychogenic purpura”. Treatment included glucocorticoids and immunomodulators, supplemented by anti-infective and renal replacement therapy, and the patient’s ecchymosis gradually subsided and resolved after one month of follow-up. This case highlights the complexity of diagnosing psychogenic purpura and the significance of medical history in the diagnosis. Only accurate and timely diagnosis can effectively avoid unnecessary treatment.